Comparative Positioning of SMEs in Bangladesh, Thailand and the Philippines - Ali, Muhammad Mahboob; Rattanawiboonsom, Vichayanan; Perez, Candido M.; Khan, Abdullah Abusayed (Economy of Regions, 2017)
Small and Medium Enterprises (SMEs) play a significant role in the nation’s economic development process. SMEs provide job opportunities, create wealth, promote modernization and contribute to technological changes. The Asia-Pacific Region is foreseen to be the next economic boom. A comparison of SMEs in Bangladesh, Thailand and the Philippines on their SMEs Landscape, Banking sector, Non-Banking sector and Capital Markets would give a picture of which strengths, weaknesses, opportunities and threats these countries face. The time period of the study is from August 2016 to January 2017. Based on the secondary sources of data, the research was conducted to examine real scenarios. The study aimed at getting information whether each country would have any benchmark to attain the best practices. The study found that SMEs credit and repayment schemes in these countries need to be gradually improved. Through proper utilization of SMEs, these countries can alleviate poverty and attain economic progress. Unfortunately, the informal sector of these countries is playing a large role. It should be transformed to formal sector by financial inclusion. This can be achieved by setting up SMEs in the formal sector.The creation of employment along with poverty reduction in the formal sector will enhance economic growth as well as fulfill the basic needs and create empowerment of people. Community banking is suggested to be introduced for accumulating micro-savings and allocating, distributing setting up SMEs in the formal sector through micro investment under the umbrella of community banking. Further, under the regional cooperation flagship of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation (BIMSTEC) Bangladesh and Thailand may work in collaborative manner in the SMEs sector. The Philippines may join the regional body of BIMSTEC and collaborate with SMEs at the regional level. This may lead to achieve some goals of sustainable development goals (SDGs). SMEs can work more rigorously for lower income group people to improve their living standard. The further research on these three countries can consider primary sources of data to find out the way to implement community bank for transforming micro savings to micro investment for removing income inequality, disparity and attaining social justice.